Development of automatic control system of drum boiler on the basis of fuzzy controller with pid-controller adaptation - Umurzakova Dilnoza; Abdullayev Timurbek; Khakimov Akhror; Qadamova Zulayho (E3S Web of Conferences, 2024)
The aim of the study is to reduce energy losses in a drum steam boiler by introducing an automatic control system realized on the basis of fuzzy adaptation of proportional-integral-derivative (PID) controller coefficients using fuzzy term-multiplications. Control algorithms of the main technological parameters of the boiler unit (air quantity, fuel quantity, steam pressure, feed water flow rate), reducing energy costs due to the maintenance of the ratio of fuel and air pressure in accordance with the mode map of the boiler unit (optimal technological process of combustion and steam formation in a steam boiler) are developed. The structural scheme of the object control is offered, in which, besides regulation of values of technological parameters, full compensation of mutual influence of all regulation circuits is made.